2020
DOI: 10.1161/atvbaha.120.314102
|View full text |Cite|
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus Is Independently Associated With Decreased Neural Baroreflex Sensitivity

Abstract: Objective. Impaired baroreflex function is an early indicator of cardiovascular autonomic imbalance. Patients with type 2 diabetes (T2D) have decreased baroreflex sensitivity (BRS), however, whether the neural and/or mechanical component of the BRS (nBRS and mBRS, respectively) is altered in those with high metabolic risk (HMR, impaired fasting glucose and/or metabolic syndrome) or with overt T2D, is unknown. We examined this in a community-based observational study, the Paris Prospective Study III. Approach a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
(58 reference statements)
2
12
0
Order By: Relevance
“…We speculated that BRS dysfunction in DM and AN could cause a change from phaselead to phase-lag. Furthermore, in line with previous studies, baroreflex response was reduced, and the delay was prolonged (Javorka et al, 2011;Xiao et al, 2019;Cseh et al, 2020), which supported the assumption. Therefore, we proposed an advanced cross-correlation function to estimate BRS in healthy and DM groups.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We speculated that BRS dysfunction in DM and AN could cause a change from phaselead to phase-lag. Furthermore, in line with previous studies, baroreflex response was reduced, and the delay was prolonged (Javorka et al, 2011;Xiao et al, 2019;Cseh et al, 2020), which supported the assumption. Therefore, we proposed an advanced cross-correlation function to estimate BRS in healthy and DM groups.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study reviewed approaches to measure baroreflex sensitivity (BRS), using the sequence method, cross-correlation method, cross-spectral method, synchronization index, cross multiscale entropy, joint symbolic dynamics, similarity index, etc., in DM. The study revealed that DM has baroreflex impairment with reduced baroreflex response and prolonged baroreflex (Javorka et al, 2011;Xiao et al, 2019;Cseh et al, 2020). Abnormal baroreflex function could indicate autonomic cardiovascular imbalance early (Ziegler et al, 2018;Cseh et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Whether T2D impairs arterial and cardiopulmonary baroreflex function during exercise has not been directly tested (Figure 2). Several studies indicate that T2D attenuates cardiac baroreflex sensitivity at rest (Holwerda et al, 2016b;Cseh et al, 2020;Kuck et al, 2020). However, this may not be specific to T2D, as weight-matched controls also exhibit impaired cardiac baroreflex control at rest compared to lean controls suggesting that obesity rather than T2D impairs arterial baroreflex control of HR (Holwerda et al, 2016b).…”
Section: Neurovascular Dysregulation During Exercise In Type 2 Diabetesmentioning
confidence: 99%
“…Most T2D also have high blood glucose, which is associated with a higher risk of all-cause mortality, especially due to severe cardiovascular events ( 5 ). In addition, T2D has been associated with deleterious effects on nerve fibers that make up the autonomic nervous system (ANS) ( 6 , 7 ), which might be associated with further health risks.…”
Section: Introductionmentioning
confidence: 99%